The Controversy Between Universal and Particular Human Rights in The Context of Indonesia - Indah Harlina; Jum Anggariani; Tetti Samosir; Utji Sri Wulan Wuryandari; Ahmad Dahlan (UIN Sunan Gunung Djati, 2026)
This study examines the dialectic between the concepts of universal and particular human rights in the Indonesian context. Through an analysis of legal documents, historical treatises, and constitutional practices, the study reveals how Indonesia developed a